1985
DOI: 10.1021/ac00291a021
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of retention for small molecules in the polystyrene/toluene and polystyrene/tetrahydrofuran systems

Abstract: The enthalpy of lnteractlon between test solutes and swollen polystyrene has been measured for toluene and tetrahydrofuran (THF) moblle phases. All solutes thermodynarnlcally prefer the statlonary phase when toluene Is the mobile phase, and pure slze-exciusion chromatography (SEC) never occurs. This surprislng result contradicts the "iike~issolves-like" approach to choosing moblie phase systems for size-excluslon chromatography. Tetrahydrofuran functions well for SEC, probably due to hydrogen-bonding effects I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…This indicates that resolving the nested fragment set from the labeled ddNTPs in a low ionic strength solution cannot be achieved. Temperature should not affect the elution volume in SEC. , In low ionic strength solutions, aromatic or ionic interactions are expected to play an important role in these separations. By replacing the 1/100× TBE buffer with a 1× TE buffer to increase the ionic strength (Figure c), it is clear that one can obtain baseline-resolved separation and improved peak symmetry for both peaks.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that resolving the nested fragment set from the labeled ddNTPs in a low ionic strength solution cannot be achieved. Temperature should not affect the elution volume in SEC. , In low ionic strength solutions, aromatic or ionic interactions are expected to play an important role in these separations. By replacing the 1/100× TBE buffer with a 1× TE buffer to increase the ionic strength (Figure c), it is clear that one can obtain baseline-resolved separation and improved peak symmetry for both peaks.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent work has shown that pure, entropycontrolled size exclusion occurs in far fewer cases than previously thought, especially for small molecules (26)(27)(28)(29)(30), and that a completely satisfactory elucidation of the SEC mechanism has yet to be demonstrated. So, in the light of these studies, the classical definition of size-dependent elution will have to be considered somewhat arbitrary in the absence of rigorous thermodynamic evidence.…”
Section: Resultsmentioning
confidence: 96%
“…The effect of bulky alkyl substituents in minimizing nonsize retention of PAC has been observed in previous studies (2,8,12,14); however, the introduction of molecular bulk with halogen substituents led to remarkable results illustrated in Figure 6. Comparing the retention of 1-(bromomethyl)naphthalene [27] with its isomer, l-bromo-4-methylnaphthalene [28], in Figure 6, reveals that the isomer with bromine attached directly to the ring [28] elutes much later than the one with a bromine attached to a methyl carbon [27]. This strongly suggests that when bromine is directly substituted on an aromatic moiety, an electronic effect comes into play that counteracts the steric effect introduced by the atom's bulk.…”
Section: Resultsmentioning
confidence: 98%
“…t 0 is the dead volume or void volume. Adams and Bicking 22 used the same approach to analyze the adsorption in SEC columns observing zero enthalpic contributions for noninteracting species through analysis of temperature effects.…”
Section: Introductionmentioning
confidence: 99%
“…The latter may be due to either simple London dispersion forces or specific polar interactions between the benzene rings of the stationary phase and a hydrogen donor such as an alcohol or carboxylic acid group. Early work by Adams and Bicking details this by analyzing different eluents and the effect of temperature on the elution showing marked effects even for relatively simple molecules. Furthermore, the stationary phase will swell differently in different solvents affecting the void volume of the column (see details below).…”
Section: Introductionmentioning
confidence: 99%